Latent profiles of autism symptoms in children and adolescents with Down syndrome. Issue 3 (4th January 2022) - Fidler, D. J.; Prince, M. A.; Van Deusen, K.; Esbensen, A. J.; Thurman, A. J.; Abbeduto, L.; Patel, L.; Mervis, C.; Schworer, E. K.; Lee, N. R.; Edgin, J. O.; Hepburn, S.; et al.
Abstract: Background: Down syndrome (DS) is associated with elevated rates of autism spectrum disorder (ASD) and autism symptomatology. To better characterise heterogeneity in ASD symptomatology in DS, profiles of caregiver‐reported ASD symptoms were modelled for children and adolescents with DS. Methods: Participants ( n = 125) were recruited through several multi‐site research studies on cognition and language in DS. Using the Social Responsiveness Scale‐2 (SRS‐2; Constantino and Gruber 2012), two latent profile analyses (LPA) were performed, one on the broad composite scores of social communication and interaction and restricted interests and repetitive behaviour, and a second on the four social dimensions of social communication, social motivation, social awareness, and social cognition. Results: A three‐profile model was the best fit for both analyses, with each analysis yielding a low ASD symptom profile, an elevated or mixed ASD symptom profile and a high ASD symptom profile. Associations were observed between profile probability scores and IQ, the number of co‐occurring biomedical conditions reported, sex, and SRS‐2 form. Conclusions: Characterising heterogeneity in ASD symptom profiles can inform more personalised supports in this population, and implications for potential therapeutic approaches for individuals with DS are discussed.